Tolerance-based evaluation of a Shariah-compliant rehabilitation IoT framework for post-stroke hand gesture monitoring - Zainuddin, Ahmad Anwar; Islam, Md Sariful; Handayani, Dini Oktarina Dwi; Kamarudin, Saidatul Izyanie; Mohd. Tamrin, Mohd. Izzuddin; Misman, Ahmad Fatzilah (IEEE, 2026)
The lack of affordable, continuous, and inclusive rehabilitation services creates disparities in patient outcomes, particularly for vulnerable groups, and raises concerns about fulfilling the ethical responsibility to ensure fair and compassionate healthcare delivery. To address these challenges within a Shariah-compliant healthcare framework, this study introduces a computational approach using the Rehabilitation Internet of Things (RIoT) to enable remote, ethical, and Patientcentred rehabilitation. Hand Gesture-based data from 200 poststroke patients at Putrajaya Hospital were collected using the MediaPipe Pose framework for real-time skeletal and hand tracking. Features such as repetition count, and completion time were extracted and analysed through predictive models, including linear regression and ensemble methods, with validation based on tolerance-based accuracy. Tolerance-based accuracy evaluation demonstrated clinically meaningful outcomes within a 20%–30% margin of agreement with manual assessments. For hand strengthening (HS), the system achieved 71.5% accuracy at ±20% tolerance and 88.5% at ±30%, reflecting strong reliability in measuring gross motor functions. Hand opposition (HO), which relies on fine motor precision, yielded 61.5% accuracy at ±20% and 84.5% at ±30%, indicating acceptable reliability at broader thresholds despite higher variability. These results affirm that RIoT can be regarded as a clinically usable tool for remote rehabilitation monitoring, particularly under ±30% tolerance. Furthermore, significant correlations were observed between computational metrics and established clinical outcomes, confirming the reliability of the proposed framework. Beyond clinical utility, the framework ensures patient data privacy and aligns with the Maqasid alShariah in upholding ʿAdl (justice), Taysīr (facilitation of access), and preservation of Akhlāq (morality). Overall, the findings highlight the potential for ASEAN healthcare systems to adopt technology-driven rehabilitation strategies that enhance patient autonomy.